Understanding CEDAW cities: a descriptive analysis - Kammerer, Edward F., Jr. (Human rights review, 2024)
The United States is only one of eight countries, and the only Western democracy, that has not ratified the 1979 Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). Due to the failure of the US to ratify CEDAW, the Cities for CEDAW campaign encourages US municipalities to adopt the CEDAW framework locally through municipal ordinances and resolutions. This article provides a descriptive overview of CEDAW cities. Our descriptive approach will provide a comprehensive and accurate account of CEDAW cities and serve as an important and essential step for more in-depth analysis of CEDAW cities in the future. First, we identify a total of 61 CEDAW cities. Next, we ask if CEDAW cities share common characteristics. Our analysis shows that while Cities with ordinances are larger and tend to lean more Democratic, the entire universe of CEDAW cities contains significant variation.